Karakteristik Pengukuran Dead Band pada Photovoltaic Polycristalline 50 Wp di PLTS Universitas Pamulang Viktor - Vita Kurniasih; Edy Sumarno; Sunardi (CV. Multi Kreasi Media, 2025)
This study aims to analyze the characteristics of dead band measurements on a 50 Wp polycrystalline photovoltaic (PV) system at the Pamulang University Solar Power Plant (PLTS). Dead band is a phenomenon where changes in power input are not followed by significant changes in output, which often occurs in solar panel-based energy conversion systems. In this study, PV panels were tested with various levels of coverage (0%, 25%, 50%, 75%, and 100%) to simulate partial shading conditions. Voltage, current, and power measurements were carried out using a National Instruments (NI) USB-6212 integrated with LabVIEW software, while light intensity was measured with a lux meter. The results showed that increasing light intensity generally increased the panel output power, but efficiency decreased as the panel temperature increased. In addition, the larger the panel coverage area (dead band), the more significant the decrease in power produced. Dead band conditions were also identified in certain voltage and current ranges, where increasing light intensity no longer provided an increase in power. These findings provide important insights for the design and development of power management systems in solar power plants, especially in mitigating the impacts of lighting variations and partial shading, so that the stability and efficiency of the resulting energy can be improved.